ANALISIS SELF-MANAGEMENT DAN ASPEK PSIKOSOSIAL PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS: LITERATURE REVIEW - Febriani, Anisa; Bayhakki, Bayhakki; Nauli, Fathra Annis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Chronic Kidney Disease (CKD) is a serious illness in which one of the treatments is hemodialysis therapy. It requires good self-management since the patients are prone to experiencing psychosocial problems. The study aims to analyze articles on self-management and psychosocial aspects of CKD patients undergoing hemodialysis. A literature review is used as a method of the study. There are some tools used to find related articles such as google scholar, scient direct, and PubMed. The English keywords are self-management AND hemodialysis patients, and psychosocial AND hemodialysis patients. While Indonesian keywords are self-management DAN pasien hemodialisis and psikososial DAN pasien hemodialisis in the 2016-2020 period. 7 research articles are analyzed over 19,428 articles that have been screened. The literature review from 7 articles shows that the majority of respondents are aged ≥ 40 years (48.81%) and male (47.5%). Self-management’s assessment of 3 articles using different questionnaires shows that the majority of respondents have poor self-management. Besides, the results of the psychosocial aspects of 4 articles state that most respondents experience anxiety, stress, and depression while they are having good social support. It is recommended for workers in the hemodialysis unit to always encourage patients about the importance of self-management and families to provide support. It helps to reduce the psychosocial impact on patients.Keywords: Hemodialysis, psychosocial, self-management